2019
DOI: 10.12944/crnfsj.7.1.21
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase Inhibitory Effect of Fermented Fruit Juice of Morinda Citrifolia L and Combination Effect with Acarbose

Abstract: Fermented fruit juice of M.citrifoliais supposed to be the future nutraceutical beverage due to its antidiabetic and antioxidant activities. The purposes of this study were to characterize the fermented juice microbiologically and chemically and to evaluate itsα-glucosidase inhibition and radical scavenging activities in vitro. The fruit of M.citrifolia was fermented and the fruit juice was obtained and evaluated for its radical scavenging activity based on a DPPH assay. It's in vitroanti diabetic activity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The inhibition of the ethanol extract of M. calabura fruit on α-glucosidase (from Saccharomyces cerevisiae) was determined based on a modified method described in a previous report (15). Activity was expressed as IC 50 and the value was compared to that of acarbose, a synthetic inhibitor.…”
Section: Enzyme Inhibitory Activity Assays α-Glucosidase Inhibitory Amentioning
confidence: 99%
“…The inhibition of the ethanol extract of M. calabura fruit on α-glucosidase (from Saccharomyces cerevisiae) was determined based on a modified method described in a previous report (15). Activity was expressed as IC 50 and the value was compared to that of acarbose, a synthetic inhibitor.…”
Section: Enzyme Inhibitory Activity Assays α-Glucosidase Inhibitory Amentioning
confidence: 99%
“…These results suggest that acarbose had more potent inhibition activity than EEPS and WEPS. Acarbose, a prescribed antidiabetic agent, is known to act through inhibition on α -glucosidase in a competitive mode, similar to that of WEPS, as previously reported [ 17 ].…”
Section: Resultsmentioning
confidence: 70%
“…The effect of EEPS and WEPS on DPPH radicals was determined based on a method described previously [ 17 ]. Different concentrations of leaf extracts (3 mL) were prepared, and into each of these solutions was added DPPH solution in ethanol (1 mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other phenolic or non-phenolic compounds likely released or metabolized during the mixed lactic acid bacteria and yeast-based fermentation in Chicha may have also contributed to the high α-glucosidase inhibition shown in the current investigation, but more research is needed to elucidate this possibility. Simamora et al [32] have reported α-glucosidase inhibitory activity of 65.53 ± 0.75% for a 100-day fermented-based juice made with Morinda citrifolia at a 0.035 mg GAE/mL dose. Chicha samples with lower fermentation time (12 h) had comparable ranges of inhibition (53.31-75.73%) at a similar sample dose (0.034 mg GAE/mL).…”
Section: Alpha-glucosidase Enzyme Inhibitory Activitymentioning
confidence: 99%